Multidisciplinary Experiences in Renal Replacement Therapy - Nunes, Ane C.F (IntechOpen, 2022)
Renal replacement therapy (RRT) is used to replace the capacity of blood filtration, which is completely lost in end-stage renal disease (ESRD). This book examines RRT from a multidisciplinary perspective. In nine comprehensive chapters over three sections, the book shows how clinical routines, especially RRT, are increasingly focused on the translational scenario of the health sciences. Chapters discuss health and wellness, hemodialysis, and clinical biomarkers of renal disease.